High frequency of germline TP53 mutations in a prospective adult-onset sarcoma cohort. - Gillian Mitchell (Public Library of Science (PLoS), 2013)
Sarcomas are a key feature of Li-Fraumeni and related syndromes (LFS/LFL), associated with germline TP53 mutations. Current penetrance estimates for TP53 mutations are subject to significant ascertainment bias. The International Sarcoma Kindred Study is a clinic-based, prospective cohort of adult-onset sarcoma cases, without regard to family history. The entire cohort was screened for mutations in TP53 using high-resolution melting analysis and Sanger sequencing, and multiplex-ligation-dependent probe amplification and targeted massively parallel sequencing for copy number changes. Pathogenic TP53 mutations were detected in blood DNA of 20/559 sarcoma probands (3.6%); 17 were germline and 3 appeared to be somatically acquired. Of the germline carriers, one appeared to be mosaic, detectable in the tumor and blood, but not epithelial tissues. Germline mutation carriers were more likely to have multiple cancers (47% vs 15% for non-carriers, P = 3.0×10(-3)), and earlier cancer onset (33 vs 48 years, P = 1.19×10(-3)). The median survival of mutation carriers following first cancer diagnosis was not significantly different from non-carriers. Only 10/17 (59%) pedigrees met classical or Chompret criteria for LFS. In summary, germline TP53 mutations are not rare in adult patients with sarcoma, with implications for screening, surveillance, treatment and genetic counselling of carriers and family members.